THE CORRELATION BETWEEN PARENTS’ INVOLVEMENT AND STUDENTS’ ENGLISH ACHIEVEMENT OF THE EIGHTH GRADE STUDENTS OF SMP NEGERI 2 BLAHBATUH IN ACADEMIC YEAR 2021/2022 - Ni Gusti Ayu Ari Wahyuni; Dewa Ayu Ari Wiryadi Joni; Ida Ayu Made Sri Widiastuti (International Journal of Applied Science and Sustainable Development (IJASSD), 2022)
The purpose of this study was to explain the correlation between parents' involvement and students' English achievement of the eighth-grade students of SMP Negeri 2 Blahbatuh. The sample of this study is 38 students. The method of this study was a quantitative method and the technique used was the correlation technique. The data were collected from a questionnaire about parents' involvement in students' English learning and English subject score on the report book of eighth-grade students of SMP Negeri 2 Blahbatuh for the first semester in the academic year 2020/2021 which was collected from the English teacher. Both of the data were calculated with Pearson Product Moment Correlation in SPSS 26 program. The result shows that there is a positive correlation between parents' involvement and students' English achievement. It proved by the result of the correlation is 0.709 which that in the higher correlation. It means that the null hypothesis (Ho) in this research is rejected and the alternative hypothesis (Ha) which states that there is a correlation between parents' involvement and students' English achievement is accepted. In conclusion, there is a positive correlation between parents' involvement and students' English achievement.